Understanding hairy cell leukemia in the context of mature B−cell neoplasms: tumor microenvironment and extracellular vesicle contribution to disease pathogenesis - Ingangi, Vincenzo; Amoroso, Dominga; Passaro, Eugenia; Di Vaia, Vincenzo; Maltoni, Filippo; Narimanfar, Ghazal; Minopoli, Michele; Rosa, Rita; Ametrano, Mariateresa; Di Gennaro, Elena; Broccoli, Alessandro; Zinzani, Pier Luigi; et al. (Frontiers in Immunology, 2026)
Mature B-cell neoplasms constitute a biologically and clinically heterogeneous group of hematologic malignancies, defined by the clonal proliferation and accumulation of monotypic mature B lymphocytes, which may involve the peripheral blood, bone marrow (BM), lymphoid tissues, or present primarily in extranodal sites. While the pathogenesis of common subtypes, such as chronic lymphocytic leukemia, multiple myeloma, Hodgkin Lymphoma and Diffuse Large B-cell Lymphoma has been extensively studied, those of rare entities like Hairy Cell Leukemia (HCL) remains poorly understood. HCL is a distinct B-cell neoplasm marked by BM infiltration of atypical “hairy” cells, pancytopenia, BM fibrosis, and the BRAF V600E mutation, which is a defining molecular hallmark of the classic form of the disease. Analogous to solid tumors, growing evidence shows that the tumor microenvironment (TME) is a pivotal contributor in both the initiation and progression of all these malignancies. However, in rare mature B-cell neoplasms, understanding how tumor cells interact with their microenvironment, in terms of immune invasion, stromal crosstalk, and tissue remodeling, remains a challenge, partly due to the scarcity of patient samples and limited availability of preclinical models. In the context of TME, extracellular vesicles (EVs) have emerged as central mediators of intercellular communication within both solid and hematological malignancies. In line with numerous findings from solid tumors, EVs are receiving heightened attention as key mediators of disease progression, immune modulation, and treatment response in blood tumors, by modulating cellular interactions and delivering bioactive cargo in the tumor milieu. This review presents HCL within the broader spectrum of mature B-cell neoplasms, highlighting the current state of knowledge on the dynamic crosstalk between malignant B cells and their TME. Particular attention is given to EVs, which play key immuno-regulatory roles by interacting with both immune and non-immune components of the TME, including stromal cells. We explore how EVs contribute to disease pathogenesis, offering a unifying framework for integrating complex interactions that are often under-investigated in rare disease contexts. Building on this synthesis, we propose that the insights gained from well-characterized lymphoproliferative disorders may serve as a valuable foundation for investigating related yet poorly understood conditions, such as HCL. Furthermore, given the scarcity of both biological samples and reliable preclinical models for rare hematological malignancies, we highlight the strategic role of European biobanks in providing access to well-annotated clinical samples—an essential resource for fostering interdisciplinary collaboration and enabling advanced experimental modelling.